Efficacy and Safety of Cataract Surgery Combined with Ab Interno Canaloplasty and Micro-Trabecular Bypass Stent Surgery in Open-Angle Glaucoma - Porter MS; Flowers A; Wood BP; Gallardo MJ (Clinical Ophthalmology)
Matthew S Porter,1 Addie Flowers,1 Brandon P Wood,1 Mark J Gallardo2 1Texas Tech University Health Sciences Center School of Medicine, Lubbock, TX, USA; 2El Paso Eye Surgeons, El Paso, TX, USACorrespondence: Matthew S Porter, Department of Ophthalmology and Visual Sciences, Texas Tech University Health Sciences School of Medicine, 3601 4th St, Lubbock, TX, 79430, USA, Tel +1-806-742-2011, Email matt.porter@ttuhsc.eduPurpose: To evaluate the effectiveness of canaloplasty via an ab-interno technique using the iTrack (Nova Eye Medical, Fremont, USA) combined with microtrabecular bypass stent surgery with the Hydrus microstent (Ivantis, Inc, Irvine, CA) following cataract surgery (CE) in patients with primary open-angle glaucoma (POAG).Methods: A retrospective, two-center, case series of 51 POAG eyes that underwent phacoemulsification followed by canaloplasty combined with microtrabecular bypass stent surgery. Eyes were categorized according to IOP and disease severity. A subgroup of patients on 3+ medications at baseline was included. Primary end points included the mean IOP and mean number of medications at 12 months, 24 months and at the last follow-up.Results: Baseline IOP (mmHg) and number of medications were 19.1± 4.0 and 2.3± 1.2 and reduced to 13.9± 2.6 (p< 0.001) and 1.2± 1.4 (p< 0.001) at 12 months, 13.7± 2.0 and 1.5± 1.5 (p< 0.001, p=0.008, respectively) at 24 months (n=31) and 14.4± 3.2 and 2.1± 1.5 (p< 0.001, p=0.5, respectively) at 36 months. In the uncontrolled group (n=27), baseline IOP and number of medications were 21.9± 3.1 and 1.9± 1.3 and reduced to 14.6± 4.2 (p=0.006) and 1.7± 1.6 (p=0.821) at 36 months postoperatively. Baseline IOP and number of medications of severe patients (n=12) were 19.0± 4.8 and 1.9± 1.1. IOP reduced to 12.8± 2.4 (p=0.005) at 12 months while the number of medications did not show any statistically significant change: 1.9± 1.6 (p=0.4). No eyes underwent additional glaucoma surgery in the study period.Conclusion: Canaloplasty combined with microtrabecular bypass stent surgery following cataract extraction demonstrated efficacy in reducing IOP and medication burden up to 24 months postoperatively. IOP reduction was also sustained up to 36 months postoperatively. The combined MIGS procedure is also effective in eyes with uncontrolled glaucoma.Keywords: intraocular pressure, glaucoma medications, canaloplasty, microtrabecular bypass stent, primary open-angle glaucoma